C'est pas dans la tête : les injustices épistémiques dans les soins aux personnes qui ont des troubles psychiques - Audrey Linder; Émilie Bovet
A recent review of the literature has shown that one of the reasons for excess mortality among people with mental disorders is less access to somatic care (Gandré et al., 2022). This article explores the testimonial injustices by people living with mental health problems and their repercussions on their somatic care, through analyzing the accounts of people affected by mental disorders, psychiatric caregivers and nursing students. It also proposes a device to bring (future) caregivers to question their own practices regarding the testimonial injustices experienced by people with mental disorders. Finally, it is an opportunity to think about addressing this theme in pre- and post-graduate healthcare training to improve the cares of people concerned by this issue.